Design and experiment of a vegetable plug seedling planting mechanism combining non-circular gear system and multi-link - Wang, Lei; Lin, Zhiwen; Zhou, Zhihan; Yu, Gaohong; Yang, Zeyu; Yu, Xuefu; Ye, Bingliang (International Journal of Agricultural and Biological Engineering, 2025)
To meet the requirements of low damage and high seedling-standing of vegetable plug seedlings during mechanical transplanting, a new seedling planting mechanism combining non-circular gear system and multi-link was developed, which consisted of a five-bar seedling pushing mechanism with the planetary gear train of non-circular gears and a cam linkage seedling supporting mechanism. Based on the agronomic requirements for transplanting vegetable plug seedlings, the design requirements and the poses of four key points of the seedling pushing mechanism were determined. The mechanism solution region synthesis method was applied to conduct precise four poses synthesis of the five-bar seedling pushing mechanism. Based on four key pose points and five additional positions of the seedling pushing trajectory, the angular variation curve of the connecting rod relative to the planetary carrier was derived through cubic B-spline curve fitting. Subsequently, the kinematics analysis of the seedling pushing mechanism was performed to complete continuous motion discrimination and determine the parameters of the five-bar seedling pushing mechanism. The kinematics model of the planetary gear train with non-circular gears was established, and the pitch curve design for each gear was undertaken to fulfill the design of the seedling pushing mechanism. According to the motion law of the seedling pushing mechanism and the seedling planting requirements, the kinematics model of the seedling supporting mechanism was established and its parameters were solved. The virtual simulation analysis and prototype experiment of the mechanism confirm that the simulation and test motion trajectory and key poses are basically consistent with the theoretical design results. Moreover, when the rotation speeds of the seedling planting mechanism are 60-80 r/min, the success rates of broccoli and pepper seedling planting all reach over 93%, indicating the correctness of the seedling planting mechanism design and its application feasibility and universality. Keywords: vegetable plug seedling transplanter, seedling planting mechanism, solution region synthesis, planetary noncircular gear train, five-bar mechanism DOI: 10.25165/j.ijabe.20251803.9229 Citation: Wang L, Lin Z W, Zhou Z H, Yu G H, Yang Z Y, Yu X F, et al. Design and experiment of a vegetable plug seedling planting mechanism combining non-circular gear system and multi-link. Int J Agric & Biol Eng, 2025; 18(3): 124–134.